Heritability of periodontitis: A systematic review of evidence from animal studies. (January 2020) - Nibali, L.; Almofareh, S.A.; Bayliss-Chapman, J.; Zhou, Y.; Vieira, A.R.; Divaris, K.
Highlights: Over a third of the phenotypic variance of periodontitis in animal studies is due to genetic factors. The estimated heritability of periodontitis in experimental animal studies seems higher than the estimate from human studies. This review confirms that a substantial amount of the variation in the risk of periodontitis is due to heritable factors. Abstract: Objective: The aim of this study was to quantify the heritability of periodontitis via a systematic appraisal of the existing evidence derived from animal studies. Design: A search was conducted through the electronic databases MEDLINE, Embase, LILACS, Cochrane Library, Open Grey, Google Scholar and ResearchGate, complemented by a hand search, for studies reporting measures of heritability of periodontitis. After full-text reading, 7 studies conducted on animal models met the inclusion criteria. Six studies carried out experimental periodontitis models in mice, while one study assessed bone loss in dry skulls of baboons with known pedigrees. Results: Heritability of 'naturally-occurring bone loss' (3 studies, non-experimental conditions) was estimated at 0.39 (95% confidence interval: 0.13-0.64) with virtually no heterogeneity (I 2  = 0%, p = 0.97). Heritability of experimental periodontitis in mice (6 studies) was 0.43 (0.28-0.58) with considerable heterogeneity (I 2  = 96%, p < 0.01). There was no evidence of publication bias. Conclusions: Over a third of the phenotypic variance of periodontitis in animal studies is due to genetic factors, somewhat higher than the estimate from human studies. It can be argued that, under the strictly-controlled experimental conditions of laboratory-induced periodontitis, the relative role of heritable factors predisposing to periodontitis and bone loss may be stronger compared with human studies.